2021
DOI: 10.1001/jama.2021.4609
|View full text |Cite
|
Sign up to set email alerts
|

Remote Research and Clinical Trial Integrity During and After the Coronavirus Pandemic

Abstract: Approximately 1 year ago, in March 2020, clinical trials were suddenly and severely disrupted by the COVID-19 pandemic. Pandemic-related restrictions that limited or prevented in-person visits resulted in unprecedented obstacles to clinical trial enrollment, data collection, and intervention delivery for many clinical trials. 1 As of April 21, 2021, ClinicalTrials.gov listed 1773 suspended clinical trials, with many trials identifying the COVID-19 pandemic as the primary reason for suspension. Ongoing trials t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 12 publications
0
61
0
Order By: Relevance
“…The results of our simulations demonstrate the potential utility of various adaptations that might be made to maintain the validity and integrity of treatment trials disrupted by COVID-19 [ 9 ], including the use of remote outcome measures and interventions [ 10 ]. Clearly, continuing a trial after a pause is a substantially better option than prematurely ending it and analyzing truncated trial data, even in the face of increased dropouts, medication disruptions, missing outcomes, and other exigencies.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our simulations demonstrate the potential utility of various adaptations that might be made to maintain the validity and integrity of treatment trials disrupted by COVID-19 [ 9 ], including the use of remote outcome measures and interventions [ 10 ]. Clearly, continuing a trial after a pause is a substantially better option than prematurely ending it and analyzing truncated trial data, even in the face of increased dropouts, medication disruptions, missing outcomes, and other exigencies.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Automated online recruitment was much quicker and less resource-intensive than face-to-face recruitment and is highly appropriate in the context of the coronavirus pandemic. 19 The credentials of a research team are important to participants, 20 and should feature on online recruitment adverts.…”
Section: Discussionmentioning
confidence: 99%
“…Despite study challenges related to the pandemic, including time and effort adapting to a remote protocol, remote recruitment and remote visits for this study were found to constitute a successful approach. We also recognize the potential advantages to participants in accessing our study remotely, including lessening the burden of time, costs, and inconvenience associated with traveling for in-person visits at the clinic [14]. It is important to note, however, that there are limitations to remote delivery of study visits, which may pose challenges for generalizing to other research studies or clinical settings that may not offer remote care.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we highlight the ways in which our study team has adapted our research protocol and study procedures so that we can continue recruitment, assessment, and intervention remotely during the COVID-19 pandemic. Remote study participation may have potential advantages for participants, including lessening the burden of travel time, costs, and inconvenience associated with in-person visits [14].…”
Section: Covid-19 and Women's Healthmentioning
confidence: 99%